Analisis Fungsi Manajamen Dalam Pelayanan Di Optik Nusantara Jambi - Dolly imam Suryanta (CV. ITTC INDONESIA, 2024)
The management function in an organization is needed to be able to measure and evaluate the efficiency and effectiveness of service activities carried out, so that the organization's goals can be achieved. This paper discusses the Analysis of Management Functions in Services at Optik Nusantara Jambi. This research aims to analyze the implementation of management functions at Optik Nusantara Jambi which have been running so far, whether they have been implemented well or have not yet been implemented in refraction and optician services. This research data was collected through observation, interviews and documentation. Meanwhile, the data analysis used by researchers is descriptive qualitative which includes data reduction, data presentation and drawing conclusions. The results of this research show that the management function in terms of planning, organizing, actuating and controlling indicators at Optik Nusantara Jambi is good in terms of health services because all forms of services carried out always refer to Operational Standards. The optical procedures that have been determined, and the implementation of the main tasks of each work unit, each part of the organizational structure, all elements and all staff have been carried out very well. Based on the results of this research, there are several suggestions that may be useful (1) Services at Optik Nusantara Jambi should continue to evaluate and innovate in their services to continue to meet the needs of Optik customers which continue to grow, especially with online sales and increasingly innovative market places. (2) Consider periodic restructuring of the Optik Nusantara Jambi organization. (3) Increasing training and continuous development for staff and Refraction Opticians regarding new optical technologies such as lens materials, lens design, understanding and other skills in Optician services